Employment: a determining factor in human development - Ruiz Guajala, Mery (2018)
This article arises from the need to analyse the employment relationship with the Human Development Index (HDI) in Ecuador in availability of data from official sources since 2005-2017. The behavior of the variables over time is described and the economic analysis is carried out where the Ordinary Least Squares and ARIMA models are structured. The results of this study show that employment is a fundamental factor for human development and social welfare. DOI: https://doi.org/10.31164/bcoyu.17.2018.666 URL: http://revistas.uta.edu.ec/erevista/index.php/bcoyu/article/view/666